Research impact and productivity of Benin according to the Science Citation Index Expanded (1973 to 2018) - Monge-Nájera, Julián (2020)
Introduction: In Benin, a tropical West African country of 11 million inhabitants where the economy is based on agriculture, the only bibliometric work available has focused on the role of collaboration among researchers, but there are no general long term studies of the country’s scientific output. Objective: To analyse the scientific output of Benin, according to the Science Citation Index Expanded, in a 46-year period. Methods: We searched for “Benin” in the country/region field of the index and analysed the results with descriptive statistics. Results: We found 4 557 documents, published between 1973 and 2018. They closely match the trends previously found in other small tropical countries: domination of articles over other types of publication like letters and notes; increase in total number of articles published each year; small collaborations in large American and European projects; and a long article lifespan that reflects the relatively slow accumulation of scientific research in tropical regions. Considering the size of the country’s economy, Benin has a good level of scientific productivity. Conclusion: In its scientific activity, Benin is similar to other tropical countries, and would benefit from increased cooperation among local researchers; from less dependence on small participations in international megaprojects, and from opening the door to research in areas of innovation rather than just solving immediate problems.